AKTUALISASI AKHLAK DALAM MENCAPAI HUMANISME-PLURALIS - Ismail, Ismail (STAIN Pamekasan, 2009)
Abstract: Akhlak (morality) is the most substansial device to perform the roles of human both as the Gods and as the social creations. Akhlak is the source of goodness, due to the fact that Muhammad, the prophet, had been considered the akhlak perfector. Akhlak is an individual humanization tool to interact with social community, however, the life wolud be catastrophizing without akhlak. Moral decadence accuring in this era is the impact of the lack of akhlak actualization. Education, which its role is to promote akhlak, is fail to operate it. Afterall, it needs to revitalize the role of education in promoting akhlak to be actualized in the Indonesian plural life.